Full Range Dielectric Characteristics of Calcium Copper Titanate Thin Films Prepared by Continuous Composition-Spread Sputtering - Kang, Hyo Min; Baek, Seung-Hyub; Song, Jong Han; Cho, Yong Soo; Choi, Ji-Won (AMER CHEMICAL SOC, 2014)
Perovskite CaCu3Ti4O12 has drawn a great deal of attention for various electronic applications due to its giant dielectric property as well as a strong stability in a wide range of temperature. In this paper, we use an off-axis continuous composition-spread (CCS) sputtering method to investigate the full range dielectric characteristics of calcium copper titanate thin films. The film compositions are continuously distributed by deposition from two targets of CaTiO3 and CuTiO3. A slightly Ca-deficient, Cu- and Ti-rich film, which has a 0.9:3.2:4.3 ratio for Ca:Cu:Ti, demonstrated the best performance by showing a dielectric constant of 781 at 100 kHz. On the other hand, all other films far away from the CaCu3Ti4O12 composition showed suppressed dielectric properties. Analyses by X-ray photon spectroscopy, micro-Raman microscopy, transmission electron microscopy, and Rutherford backscattering spectroscopy reveal that there are three possible origins for such superior performance at off stoichiometric thin films: (1) bulk doping by excessive Cu and Ti ions, (2) chemically modified grain boundary, and (3) the lowered electrode sample interface resistance. Our result will provide a new insight into engineering the dielectric properties using off-stoichiometric synthesis.
Keywords: GIANT PERMITTIVITY; CACU3TI4O12; GRAIN; CONSTANT; TEMPERATURE